(untitled) (Revista Contexto & Educação, 2023)
This study aimed to analyze the perception of students, teachers and managers about the teaching practices adopted in Higher Education, and their implications in the teaching-learning process of students in Engineering. 208 professors, 460 students and 9 managers from a Brazilian university participated in this investigation. The research design was based on a mixed approach, combining different types of methods of a quantitative and qualitative nature, using different data collection techniques. The results suggest that many teachers and administrators joined in a circumstantial way and that their teaching practices are centered on their experiences as students. Students point to a need for change in the didactic and pedagogical practices of teachers since the profile of students always changes. Data suggest that some teachers seek to innovate their methodologies, however, teachers have encountered challenges such as: the excessive number of students per class; lack of diverse learning spaces; lack of knowledge of teaching-learning and assessment techniques as well as active learning methodologies; and the lack of financial resources. Finally, the participants of the Brazilian university point to the need for future training in the didactic-pedagogical scope so that they can adapt their teaching practices.